A gall-forming biological control agent suppresses vegetative growth of an invasive tree. Issue 11 (1st November 2016) - Tipping, Philip W.; Martin, Melissa R.; Gettys, Lyn A.
ABSTRACT: Attack by the gall-forming biological control agent Lophodiplosis trifida Gagné (Diptera: Cecidomyiidae), reduced Melaleuca quinquenervia sapling height by 10.1%, leaf biomass by 42%, woody biomass by 42.7%, and root biomass by 30.3%. This provided the first quantitative evidence of the potential of L. trifida to suppress pre-reproductive M. quinquenervia .